MOBILE LEARNING TO LEARNINGS: FUNCTION AND BENEFITS - Endang Suparman; Kapraja Sangadji (International Journal of Education, Information Technology, and Others, 2020)
Mobile learning as the intersection of mobile computing and e-learning: accessible resources wherever you are, strong search capabilities, rich interaction, powerful support for effective learning, and performance-based assessment. In the concept of learning mobile learning brings the benefits of the availability of teaching materials that can be accessed at any time and visualization of interesting material. The important thing to note is that not every teaching material is suitable to use mobile learning. The greatest added value of mobile learning vis-a-vis PC learning lies in the aspects that extend classroom interaction to other locations via communication networks. There are three functions of Mobile Learning in classroom learning activities (classroom instruction), namely as supplementary which is optional, complementary, or substitute